GREEN TECHNOLOGY ADOPTION IN MALAYSIA: WHERE ARE WE NOW? WHAT IS LACKING? & WHAT SHOULD WE DO NEXT? - Muhammad Shabir Shaharudin; Yuvaraj Ganesan; Yudi Fernando; Hasnah Haron, (JOURNAL INFORMATION AND TECHNOLOGY MANAGEMENT (JISTM), 2024)
There have been numerous studies on the adoption of green technology, particularly in the manufacturing industry. Nevertheless, the evidence of green technology being used by firms in Malaysia is still limited. The research objective is to investigate green technology adoption in Malaysia from the literature in order to understand what green technology has been adopted. This study performed a systematic literature review and bibliometric analysis to answer the research objective. The database chosen to undertake this study is Scopus, Web of Science and Lens.org. Findings show that i) most studies in the literature is still focusing on the adoption or acceptance of green technology by firms, ii) most studies are written for management focus, and iii) energy and construction industry being the most investigated area of research. The literature gaps are showing that Malaysia green technology adoption is still in the infant stage. Currently, the literature is stagnant with many conceptual papers only contributing to the first level of green technology perception. Future research should focus on providing empirical evidence of green technology adoption.